2019
DOI: 10.3389/fmicb.2019.01092
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Quercetin Increases Colonic Microbial Diversity and Attenuates Colitis Severity in Citrobacter rodentium-Infected Mice

Abstract: Disturbed balance between microbiota, epithelial cells, and resident immune cells within the intestine contributes to inflammatory bowel disease (IBD) pathogenesis. The Citrobacter rodentium -induced colitis mouse model has been well documented. This model allows the analysis of host responses to enteric bacteria and facilitates improved understanding of the potential mechanisms of IBD pathogenesis. The current study evaluated the effects of dietary 30 mg/kg quercetin supplementation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 42 publications
3
74
0
Order By: Relevance
“…Notably, several investigations have also identified the dietary intake of polyphenols as a potential option for CVD management (Tangney and Rasmussen ; Ding et al ). Epidemiological studies have also correlated a decreased risk of CVD onset with an increased intake of dietary quercetin, a natural flavonoid compound found in vegetables and fruits (Peterson et al ; Hong and Piao ; Lin et al ). This correlation is supported by a preclinical study in which the administration of a quercetin supplement reduced the progression of atherosclerosis (Shen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several investigations have also identified the dietary intake of polyphenols as a potential option for CVD management (Tangney and Rasmussen ; Ding et al ). Epidemiological studies have also correlated a decreased risk of CVD onset with an increased intake of dietary quercetin, a natural flavonoid compound found in vegetables and fruits (Peterson et al ; Hong and Piao ; Lin et al ). This correlation is supported by a preclinical study in which the administration of a quercetin supplement reduced the progression of atherosclerosis (Shen et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have shown changes in microbial communities due to rice bran or quercetin and describe the improvement of colonization resistance and reduction of colon cancer (11, 14, 53). However, these studies are marked by high variations of the microbiota composition likely due to host factors.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae and Fusobacteriaceae were reported to be positively related to quercetin supplementation whereas Suttrellaceae and Oscillospiraceae were found to be negatively correlated (26). However, Lei et al, (2019) reported an increase in abundances of Bifidobacterium, Bacteroides, Lactobacillus and Clostridium , with a reduction of Fusobacterium and Enterococcus in mice fed with quercetin (11). With higher resolution and removal of host factors, our results contrast with both studies and show enrichment of Acidaminococcus intestini and decreased abundances of E. limosum, E. faecalis, A. caccae, D. longicatena and C. catus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations